2020
DOI: 10.16984/saufenbilder.566377
|View full text |Cite
|
Sign up to set email alerts
|

Sex Prediction Using Finger, Hand and Foot Measurements for Forensic Identification in a Nigerian Population

Abstract: In forensics, the identification of recovered human remains is important and of great significance. Sex determination is the most important primary parameter in human identification. We investigated the predictive role of the anthropometric measurements of hand, finger and foot dimensions in sex determination. The main objective was to correlate sexual dimorphism with hand, finger and foot dimensions and determine their sectioning point(s) and also ascertain the variables which can better predict sex. A cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Morphological gender differences in fingers length have been illustrated in different studies as in Aboul Hagag et al (2011), Habib and Kamal (2010) and Kanchan et al (2010). The mean of middle finger length in the present study was 7.66 ± 0.47 in RMF in females and 8.22 ± 0.50 in males while the mean in LMF in females was 7.68 ± 0.45 and in males was 8.30 ± 0.42 that in comparison with Iroanya et al (2020) in which the mean values were RMF 7.48±0.65 in females and 8.1 ± 0.64 in males while LMF 7.5 ± 0.67 in females and 8.17±0.67 in males and this slight variation can be attributed to influence of population and ethnic variability.…”
Section: Discussionsupporting
confidence: 50%
“…Morphological gender differences in fingers length have been illustrated in different studies as in Aboul Hagag et al (2011), Habib and Kamal (2010) and Kanchan et al (2010). The mean of middle finger length in the present study was 7.66 ± 0.47 in RMF in females and 8.22 ± 0.50 in males while the mean in LMF in females was 7.68 ± 0.45 and in males was 8.30 ± 0.42 that in comparison with Iroanya et al (2020) in which the mean values were RMF 7.48±0.65 in females and 8.1 ± 0.64 in males while LMF 7.5 ± 0.67 in females and 8.17±0.67 in males and this slight variation can be attributed to influence of population and ethnic variability.…”
Section: Discussionsupporting
confidence: 50%
“…In this study, it is thought that the higher data and the feature extraction method used cause this high recognition rate. There are many studies for person recognition from hand vein images [36][37][38][39][40]. However, since these studies are not directly related to the present study, they have not been compared in detail.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study reported a sex bias of 6.9% and −19.6% for left-hand length and hand breadth respectively [ 6 ] while Ishak, Hemy [ 7 ] reported a sex bias of −4.5% and −1.1% for hand length and hand breadth respectively. Sex biases have also been shown in foot-based estimating models [ 8 , 9 ]. The directionality of sex bias is important for forensic and bioarcheological studies.…”
Section: Introductionmentioning
confidence: 99%